Literary theory : a practical introduction - Ryan, Michael, 1951- (How to study literature, 2017)
Literary Theory: A Practical Introduction, Third Edition, presents a comprehensive introduction to thefull range of contemporary approaches to the study of literature and culture, from formalism, structuralism, and historicism to ethnic, gender, and science studies.Introduces students to a variety of contemporary approaches to the study of literature and cultureDemonstrates how the varying perspectives on texts can lead to different interpretations of the same workFeatures numerous updates that include new literary texts, new and expanded sectionsRepresents the ideal accompaniment to the upcoming Third Edition of LiteraryTheory: An Anthology.